Trends in political and journalistic tweeting during electoral campaigns: A glimpse from Nigeria's digital democracy - Ahmad, Muhammad Auwal; Ersoy, Metin; Salisu, Yakubu Mohammed; Dambo, Tamar Haruna; Dalhatu, Sadiya (Sage Publications Inc, 2025)
Extensive research has explored the evolving dynamics and influence of social media, particularly the X platform (formerly Twitter), on various aspects of political communication and journalism across borders. However, only a few studies examine trends in its use for election campaigns and journalism in sub-Saharan Africa, from the perspective of media logics and intermedia agenda-setting. To address this gap, we analyzed trends in the use of X by two presidential candidates and its integration into political reporting by three national newspapers during Nigeria's 2019 presidential campaigns: a period when the platform was pivotal in political communication and digital journalism. Findings from the analysis of 688 X-based posts reveal the changing operational logics that facilitated the increased influence of candidates-who predominantly used X for self-promotion and party-branding-on the agendas of mainstream newspapers that utilized the platform as a tool for sourcing and disseminating political news.
Keywords: Digital journalism; intermedia agenda-setting; media logics; news production; political communication; social media